Analyzing The Data Reading Interest Of Tangerang Citizens In Selecting Between Physical Books And E-Books - Puti Lenggo Ginny; Rinintha Parameswari; Diana Silaswara (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
Reading activities can be done by anyone; children, teenagers, adults, even elderly people. However, these reading activities have much ignored by various circles, especially Indonesian citizens. In an era when technologies have not developed rapidly as today, people used physical books for reading. In practice, physical books are still the main choice, especially for Tangerang people. The reading interest of Tangerang people increased significantly since 2014 to 2019. However, a solution is required to develop literacy amidst modernity in responding to the development of an all-around technology era. E-book is the manifestation of the provision of profound knowledge through digital access with all its strengths and weaknesses. This study aims to identify which one that Tangerang people are more preferred; reading physical books or e-books. This study used qualitative-descriptive method. The data sources used were the result of a 10-day online survey and literature study as the secondary data. Research results indicate that based on the categories of the easiness in obtaining reading materials, and price, e-books are more superior because they are easily obtained and affordable. However, based on the comfort-wise category, physical books still become the preference of Tangerang people because they are clearer, appealing, and prevent eyestrain